Utilization of Solar Cells as Environmentally Friendly Energy - Fitria Claudya Lahinta; Christeonaris Manases Futwembun; Gheananda Nadine Jilian Mongi; Anugerah Alexandro Golly; Rafly Manopo (Publikasi Indonesia, 2025)
The use of new and renewable primary energy is increasingly common in many countries. The use of environmentally friendly energy sources, such as solar power, is anticipated to help reduce greenhouse gas emissions and mitigate severe climate change. Based on a simple principle, which is to turn daily life into a series of activities full of energy, sunlight is an example of natural resources, therefore solar cells become an energy that can be said to be environmentally friendly. Utilizing solar panels (solar cells), sunlight has been used extensively to generate electrical power for communication satellites. These solar panels can generate energy, although they may not last for a long duration and do not require fuel. Therefore, this solar panel or solar cell can be said to be clean and environmentally friendly.